Trauma-induced coagulopathy management - Maria Grazia Bocci (AboutOpen, 2022)
In the last years significant progress has been made in the understanding and treatment of hemorrhage caused by trauma which (along with the advances made in early resuscitation, and critical care) has led to a reduction of “late” deaths, meaning those due to trauma-induced organ failure/sepsis. Depending on the case, trauma is usually characterized by a variable equilibrium between hypo and hypercoagulation, with a majority of hypercoagulation cases. Trauma-induced coagulopathy (TIC), instead, is not only characterized by a coagulation disorder but also a state of inflammation which increases the need for transfusions, the risk of multiorgan failure and thromboembolic complications. In this clinical picture, hemostatic resuscitation, damage control resuscitation and homeostasis maintenance have been shown to reduce mortality. According to guidelines, the heart of TIC treatment is an early individualised goal-directed treatment relying on coagulation support and thromboprophylactic strategies (administration of tranexamic acid, fibrinogen concentrate and packed red blood cells), platelet function monitoring and viscoelastic Point-of-care testing. The implementation of the protocol suggested by the guidelines has allowed a more effective support of coagulopathy and has led to a reduction in hemoderivatives usage, hospitalization time and the death rate in severely injured trauma patients. The aforementioned improvements in TIC management were explicitly confirmed by a multicentric study in which the year the guidelines were implemented was compared with a prior year when no specific protocol was executed.